1999
DOI: 10.1007/s101470050087
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy for stage I-II non-small cell lung cancer

Abstract: Background. Surgery has been regarded as the standard treatment for patients with non-small cell lung cancer in the early stage, while radiotherapy has become an effective alternative for medically inoperable patients and those who refuse surgery. Methods. We reviewed the records of 31 patients with stage I-II non-small cell lung cancer treated by radiotherapy between 1980 and 1997. There were 15 patients in stage I and 16 in stage II. The variables analyzed for influence on causespecific survival and loco-reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2003
2003

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…In their total study population of 31 patients Slotman et al 2 found only one patient with isolated regional nodal failure among the six patients who relapsed. Okamoto et al 9 also noted that none of their patients treated with involved field radiotherapy had an isolated mediastinal node recurrence.…”
Section: Discussionmentioning
confidence: 98%
“…In their total study population of 31 patients Slotman et al 2 found only one patient with isolated regional nodal failure among the six patients who relapsed. Okamoto et al 9 also noted that none of their patients treated with involved field radiotherapy had an isolated mediastinal node recurrence.…”
Section: Discussionmentioning
confidence: 98%